2022
DOI: 10.3390/jof8101046
|View full text |Cite
|
Sign up to set email alerts
|

The Human Mycobiome: Colonization, Composition and the Role in Health and Disease

Abstract: The mycobiome is the fungal component of the human microbial ecosystem that represents only a small part of this environment but plays an essential role in maintaining homeostasis. Colonization by fungi begins immediately after birth. The initial mycobiome is influenced by the gestational age of a newborn, birth weight, delivery method and feeding method. During a human’s life, the composition of the mycobiome is further influenced by a large number of endogenous and exogenous factors. The most important facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 165 publications
0
33
0
3
Order By: Relevance
“…Diet has an important influence on the intestinal fungi [ 8 ]. Moreover, it is a source of fungi that can pass into or even colonize the gut [ 9 ]. There are several examples that show that diet can have an influence on the gut mycobiome; for example, it was shown that mice on a high-fat diet had a different mycobiota compared to mice on a standard diet [ 10 ], and that Methanobrevibacter and Candida abundance was correlated with a high-carbohydrate diet [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diet has an important influence on the intestinal fungi [ 8 ]. Moreover, it is a source of fungi that can pass into or even colonize the gut [ 9 ]. There are several examples that show that diet can have an influence on the gut mycobiome; for example, it was shown that mice on a high-fat diet had a different mycobiota compared to mice on a standard diet [ 10 ], and that Methanobrevibacter and Candida abundance was correlated with a high-carbohydrate diet [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overall microbiome, which includes the mycobiome, has been found to be critical to various aspects of human biology, including metabolism, pathogenesis, energy pathways, immunity, neurology, and health [ 1 ]. The human mycobiome, like the microbiome, is not a static system but instead highly variable throughout life, both at the intra- and inter-individual levels [ 2 , 3 ]. Colonization begins directly from birth and continues to grow and fluctuate with factors such as exercise, daily activities, nutrition, age, sex, disease, and medical therapies (especially the use of antibiotics and antifungals) [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The human mycobiome, like the microbiome, is not a static system but instead highly variable throughout life, both at the intra- and inter-individual levels [ 2 , 3 ]. Colonization begins directly from birth and continues to grow and fluctuate with factors such as exercise, daily activities, nutrition, age, sex, disease, and medical therapies (especially the use of antibiotics and antifungals) [ 2 , 4 ]. In this review, we will specifically focus on the role of the mycobiome in women’s health and explore the various factors and implications involved in this lesser-studied part of the human microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies showed that fungi are a component of the human body’s ecosystem, described as the human “mycobiome”. Similar to the bacterial and viral microbiome, the mycobiome has a variable composition shaped by several factors [ 12 ]. The presence of the mycobiome has been detected in the gut of at least 70% of healthy adults [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two mycotypes can be distinguished in the gut. Mycotype 1 is defined by a high abundance of the genus Saccharomyces and also other unclassified genera, while mycotype 2 consists of the genera Penicillium , Malassezia and Mucor [ 12 ].…”
Section: Introductionmentioning
confidence: 99%